Preparation and Application of Hydroxyacetic Acid Esters as Methanol-Gasoline Additives - Jiang, Xiaoyan; Tang, Ying (Asian Journal of Chemistry, 2013)
In this paper, hydroxyacetic acid esters (glycolic esters) were synthesized and used as phase stabilizer and saturation vapour pressure depressor of methanol-gasoline. The results show that the stabilities of the blends depend on the length of the glycolic esters’ alkoxy group. Among these glycolic esters, hexyl glycolic ester and octyl glycolic ester were found to be the most effective in various gasoline-methanol blends. Besides, the glycolic esters display high capacity to depress the saturation vapour pressure of methanol-gasoline and decyl glycolic ester is the most effective one. According to the results, it can be concluded that the glycolic esters have the great potential to be used as bifunctional gasoline-methanol additives.